THE IMPORTANCE OF GENERAL PHYSICAL PREPARATION AND WAYS OF ITS DEVELOPMENT IN THE FORMATION OF COMPETENCE OF FUTURE FREESTYLE WRESTLERS IN SECONDARY SCHOOLS - Khanturaev, Nodir (Educational Research in Universal Sciences, 2023)
Being competent in your given sport is of utmost importance if you are to succeed. Competence brings confidence, and with both of these factors on your side, you will be ready to achieve your goals. The article covers that competence is of paramount importance in the formation of future wrestlers, as well as aims to substantiate the importance of general physical preparation and its development in the formation of competence of them. The effectiveness of the use of competencies in freestyle wrestling is ensured by general physical preparation, specific physical preparation, psychological preparation, technical preparation, tactical preparation as well as pedagogical skills. Among them, the importance of general physical preparation in forming competence for future freestyle wrestlers in secondary schools will be mentioned.